Comparative Interpretation of CT and Standard Radiography of the Chest - Coche, Emmanuel E.; Ghaye, Benoit; Mey, Johan; Duyck, Philippe; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Standard radiography of the chest remains one of the most widely used imaging modalities but it can be difficult to interpret. The possibility of producing cross-sectional, reformatted 2D and 3D images with CT makes this technique an ideal tool for reinterpreting standard radiography of the chest. The aim of this book is to provide a comprehensive overview of chest radiography interpretation by means of a side-by-side comparison between chest radiographs and CT images. Introductory chapters address the indications for and difficulties of chest radiography as well as the technical and practical aspects of CT reconstruction and image comparison. Thereafter, the radiographic and CT presentations of both anatomical variants and the diseased chest are illustrated and discussed by renowned experts in thoracic imaging. Individual chapters are devoted to the imaging features of selected common diseases and disorders, including COPD, lung cancer, pulmonary embolism and hypertension, atelectasis and chest trauma. The book is complemented by online extra material which provides many further educational examples. .
Introduction: The Remaining Indications of Chest Radiography in Clinics -- Difficulties for Chest Radiography Interpretation -- Technical and Practical Aspects for CT Reconstruction and Image Comparison: The use of Isotropic Imaging and CT Reconstructions -- The Use of PACS, Tips and Tricks for Image Comparison -- Semeiology of Normal Variants and Diseased Chest: The Mediastinum -- The Heart -- The Hilae and Pulmonary Vessels -- The Lung Parenchyma -- The Respiratory Tract -- The Pleura -- The Diaphragm -- The Chest Wall -- Selected Diseases With Peculiar Aspect on Chest Radiography: COPD -- Missed Lung Lesions -- Lung Atelectasis -- Lung cancer.-Pulmonary Embolism and Pulmonary Hypertension -- Chest Trauma -- Subject Index.
Keywords: Medicine; Radiology, Medical; Medicine & Public Health; Imaging / Radiology